Polymorphonuclear MDSCs are enriched in the stroma and expanded in metastases of prostate cancer - Jiling Wen; Gang Huang; Sheng Liu; Jun Wan; Xuechun Wang; Yini Zhu; William Kaliney; Chao Zhang; Liang Cheng; Xiaofei Wen; Xin Lu (The Journal of Pathology: Clinical Research, 2020)
Abstract Myeloid‐derived suppressor cells with polymorphonuclear morphology (PMN‐MDSCs) contribute to the progression and immune evasion of prostate cancer. However, the spatial distribution of tumor‐infiltrating PMN‐MDSCs in primary and metastatic prostate cancer, especially in the context of comparison between the epithelial and stromal compartments of the tumor, has not been characterized. Here, we describe a multicolor immunofluorescence staining study of 90 primary tumors, 37 lymph node metastases (all with matched primary tumors) and 35 bone metastases using archived samples. CD11b+ CD15+ cells were identified as PMN‐MDSCs and pan‐cytokeratin+ cells were identified as prostate epithelial cells. We found that, in both primary tumor and metastases, PMN‐MDSCs infiltrate much more readily in the stromal area compared with the epithelial area of the tumor regions. In comparison to the stromal area of primary tumors, the stromal area of either lymph node metastases or bone metastases was infiltrated with more PMN‐MDSCs. In primary tumors, stromal PMN‐MDSCs were associated with vascularization, segmented neutrophils, patient age and close juxtaposition to neoplastic epithelial cells. These results reveal the stroma rather than the epithelia of prostate cancer as the major hotbed for PMN‐MDSCs and support the role of PMN‐MDSCs in the metastatic progression of prostate cancer.